Mental Health and Exposure to the United States. Issue 9 (September 2015) - Perreira, Krista M.; Gotman, Nathan; Isasi, Carmen R.; Arguelles, William; Castañeda, Sheila F.; Daviglus, Martha L.; Giachello, Aida L.; Gonzalez, Patricia; Penedo, Frank J.; Salgado, Hugo; Wassertheil-Smoller, Sylvia
<x xml:space="preserve">Abstract</x> Abstract We examined the association between exposure to the U.S. and symptoms of poor mental health among adult Hispanic/Latinos (N = 15, 004) overall and by Hispanic/Latino background. Using data from the Hispanic Community Health Study of Latinos (HCHS/SOL), we estimated logistic regressions to model the risk of moderate to severe symptoms of psychological distress, depression, and anxiety as a function of years in the U.S. and six key psychosocial risk and protective factors. In unadjusted models, increased time in the U.S. was associated with higher risk of poor mental health. After adjustment for just three key factors—perceived discrimination, perceived U.S. social standing, and the size of close social networks—differences in the odds of poor mental health by years in the U.S became insignificant for Hispanics/Latinos overall. However, analyses by Hispanic/Latino background revealed different patterns of association with exposure to the U.S. that could not be fully explained.